MOLECULAR ANALYSIS OF FECGH GENE IN HAMDANI SHEEP BREED IN IRAQI KURDISTAN REGION - AL-BARZINJI, YOUSIF M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The objective of this study was to investigate association between FecGH-GDF-9 gene polymorphism and litter size in Hamdani fat-tailed sheep. The genomic DNA was extracted from eighty-seven blood samples of Hamdani ewes. The FecGH-GDF-9 locus was detected by PCRs, and identified DNA genotyped by DNA sequencing. The evaluate several parameters included fertility (%), conception (%), letter size at birth, twining rate (%), triple rate (%), barrenness (%) and productivity (%) were measured and arrived 91.95, 95.40, 1.825, 150, 11.25, 8.05 and 159.77, respectively. The blast tree view results in NCBI blast show Hamdani sheep is more closely to Norway white face sheep, Han sheep and Pelibuey Sheep breeds which have high litter sizes than the Iranian Ghezel sheep. Hamdani ewe’s genome have three changed nucleotides point at 1273 bp (C to G) changed Alanine to Arginine, 1281 bp (A to T) changed lysine to Isoleucine and 1344 bp (C to A) changed Proline to Glutamine. Also three nucleotides deletion were detected at 1279 bp (C), 1283 (T) and 1376 bp (G) position with two inserted nucleotides at 1319 bp (T) and 1357 bp (G) position. The 5’….C/TNAG…3’ sequence cite of mutated FecGH locus was detected by Ddel restriction enzyme which have significant effect on litter size in sheep breeds.